Sosialisasi Penggunaan E-Modul Ekosistem Dalam Pembelajaran di SMKN Perikanan Wini Kabupaten Timor Tengah Utara - Feliksitas Angel Masing; Maria Paulin Sari Dewi; Made Santiari; Lidwina Felisima Tae; Erlin Fatima Halek (UNIB Press, 2023)
The change in the learning process during the pandemic from face-to-face to online (online) is a challenge to use the right learning media, namely e-modules. This socialization activity for the introduction of the coastal ecosystem e-module will be held in November 2021 at the Wini Fisheries Vocational School. This service was attended by 13 students of class XI Freshwater Fisheries Agribusiness. This socialization activity begins with an introduction to the e-module followed by practical use. Students who take part in this socialization already know and are able to use this e-module and give a positive response to this activity